Distribution, abundance and ecology of ticks in Portugal mainland: data from five years of a surveillance program REVIVE - Santos-Silva, M.M. (2017)
Abstract in: 20th European Society for Vector Ecology Conference 2016: book of abstracts, p. 120. doi:10.3920/978-90-8686-837-7